Keanekaragaman Hama Kutu Daun Pada Tanaman Cabai Rawit Yang Ditumpang Sarikan Dengan Berbagai Populasi Kacang Tanah - Yunia Cahyani; Bambang Supeno; Dwi Noorma Putri (Universitas Khairun, 2026)
This study aims to determine the species diversity and abundance of aphids on bird's eye chili intercropped with varying populations of peanuts. The field experiment was conducted from May to November 2025 on a farmer's field. The study employed a single-factor Completely Randomized Design comprising four treatment levels, namely without peanuts (TS0) at a 1:0 ratio, 36 peanut clumps at a 1:2 ratio (TS1), 54 clumps at a 1:3 ratio (TS2), and 72 clumps at a 1:4 ratio (TS3). Each treatment was assigned to five replicates, providing 20 experimental plots in total. Four aphid species were recorded, namely Hysteroneura setariae, Aphis craccivora Koch, Myzus persicae, and Aphis gossypii. Aphid abundance was greatest in TS0, with 7,105 individuals, and lowest in TS2, with 1,890 individuals. Among the treatments, TS3 had the largest H′ value of 1.02 and an E value of 0.74, and the lowest C value was 0.44. These findings indicate that increasing peanut populations within the intercropping system tends to produce a more diverse and evenly distributed aphid community with lower species dominance than that observed in monoculture bird’s eye chili.